A philological commentary on Tacitus, Annals 14, 1-54 - Adams, J; James Noel Adams (1970)
The Commentary deals only with stylistic and linguistic matters. Textual problems are sometimes discussed, but only when they can be illuminated by points of usage. Diverse subjects are treated, but certain themes predominate. Many of the notes are concerned with the history and usage of certain words and stylistic devices down to the end of the first century A.D. Tacitus' originality and idiosyncrasies, and his indebtedness both to contemporary developments in educated usage and to the historiographical tradition, are pointed out. Archaisms, poeticisms, and words of high style are differentiated from words current among the educated classes. Tacitus' vocabulary is compared in artificiality with that of previous historians and other archaising writers of the early Empire. The Controversiae and Suasoriae of the Elder Seneca, the Institutio Oratoria of Quintilian, and the Declamations ascribed to Quintilian have been taken as evidence for the ordinary educated usage of the period. [Abstract continues in thesis ...]